Identification of oleaginous yeasts that metabolize aromatic compounds. (1st October 2020) - Yaguchi, Allison; Franaszek, Nicole; O'Neill, Kaelyn; Lee, Stephen; Sitepu, Irnayuli; Boundy-Mills, Kyria; Blenner, Mark
Abstract: The valorization of lignin is critical for the economic viability of the bioeconomy. Microbial metabolism is advantageous for handling the myriad of aromatic compounds resulting from lignin chemical or enzymatic depolymerization. Coupling aromatic metabolism to fatty acid biosynthesis makes possible the production of biofuels, oleochemicals, and other fine/bulk chemicals derived from lignin. Our previous work identified Cutaneotrichosporon oleaginosus as a yeast that could accumulate nearly 70% of its dry cell weight as lipids using aromatics as a sole carbon source. Expanding on this, other oleaginous yeast species were investigated for the metabolism of lignin-relevant monoaromatics. Thirty-six oleaginous yeast species from the Phaff yeast collection were screened for growth on several aromatic compounds representing S-, G-, and H- type lignin. The analysis reported in this study suggests that aromatic metabolism is largely segregated to the Cutaenotrichosporon, Trichosporon, and Rhodotorula clades. Each species tested within each clade has different properties with respect to the aromatics metabolized and the concentrations of aromatics tolerated. The combined analysis suggests that Cutaneotrichosporon yeast are the best suited to broad spectrum aromatic metabolism and support its development as a model system for aromatic metabolism in yeast.